SCREENING FOR MENTAL EMOTIONAL DISORDERS: DEPRESSION, ANXIETY, AND STRESS AMONG FIRST-YEAR NURSING STUDENTS - Fida Dyah Puspasari; Destianti Indah Mayasari (Nursing Sciences Journal, 2026)
Background: Mental emotional disorders such as depression, anxiety, and stress are common among university students, especially during the transition from high school to higher education. Early detection is important to prevent more severe psychological problems. Objective: This study aimed to describe the prevalence of depression, anxiety, and stress among first-year students. Methods: This study used a descriptive design with a cross-sectional approach. The research was conducted at STIKES Serulingmas Cilacap. A total of 150 first-year students were included using total sampling. Mental emotional disorders were measured using the Depression Anxiety Stress Scale (DASS-42). Data were analyzed using descriptive statistics. Results: The results showed that 30% of students experienced depression (18% mild, 9% moderate, and 3% severe). Anxiety was experienced by 67% of students (18% mild and 34% moderate). Meanwhile, 20% of students experienced stress (13% mild and 4% moderate). Conclusion: A considerable proportion of first-year students experienced mental emotional disorders. Early screening programs and psychological support services are recommended to improve students’ mental health.